Is There Really an Association of High Circulating Adiponectin Concentration and Mortality or Morbidity Risk in Stable Coronary Artery Disease - Mayer, Otto; Seidlerová, Jitka; Bruthans, Jan; Gelžinský, Julius; Rychecká, Martina; Mateřánková, Markéta; Karnosová, Petra; Wohlfahrt, Peter; Cífková, Renata; Filipovský, Jan (Hormone and Metabolic Research, 2020)
Adiponectin has several beneficial properties, namely, on the level of glucose metabolism, but paradoxically, its high concentrations were associated with increased mortality. We aimed to clarify the impact of high serum adiponectin on mortality and morbidity in patients with stable coronary artery heart disease (CAD). A total of 973 patients after myocardial infarction and/or coronary revascularization were followed in a prospective cohort study. All-cause and cardiovascular (CV) death, non-fatal cardiovascular events, and hospitalizations for heart failure (HF) were registered as outcomes. High serum adiponectin levels (≥8.58 ng/ml, i. e., above median) were independently associated with increased risk of 5-year all-cause, CV mortality or HF [with HRR 1.57 (95% CI: 1.07-2.30), 1.74 (95% CI: 1.08-2.81) or 1.94 (95% CI: 1.20-3.12), respectively] when adjusted just for conventional risk factors. However, its significance disappeared if brain natriuretic peptide (BNP) was included in a regression model. In line with this, we observed strong collinearity of adiponectin and BNP. Additionally, major adverse cardiovascular event (i. e., CV death, non-fatal myocardial infarction or stroke, coronary revascularization) incidence risk was not associated with high adiponectin. In conclusion, the observed inverse association between adiponectin concentrations and mortality risk seems to be attributable to concomitantly increased BNP, rather than high adiponectin being a causal factor.
Keywords: Cross-Sectional Studies; Prognosis; Prospective Studies; morbidita; Humans; následné studie; adiponektin; lidé středního věku; prospektivní studie; Middle Aged; míra přežití; Czech Republic; nemoci koronárních tepen; prognóza; Follow-Up Studies; Coronary Artery Disease; Risk Factors; mužské pohlaví; Česká republika; Survival Rate; průřezové studie; rizikové faktory; Adiponectin; biologické markery; ženské pohlaví; lidé; Morbidity; Biomarkers; Aged; senioři; Male; Female